2021
DOI: 10.48550/arxiv.2109.00754
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Survey of gravitational wave memory in intermediate mass ratio binaries

Abstract: The non-linear gravitational wave (GW) memory effect is a distinct prediction in general relativity. While the effect has been well studied for comparable mass binaries, it has mostly been overlooked for intermediate mass ratio inspirals (IMRIs). We offer a comprehensive analysis of the phenomenology and detectability of memory effects, including contributions from subdominant harmonic modes, in heavy IMRIs consisting of a stellar mass black hole and an intermediate mass black hole. When formed through hierarc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 65 publications
(125 reference statements)
0
3
0
Order By: Relevance
“…The strategies for detecting the GW memory effect were first proposed by Braginsky and Thorne in the 1980s [13,40]. Since the first detection of GWs by LIGO in 2015 [41], many works about detecting memory effect with current and future GW detectors have appeared [30,[42][43][44][45][46][47][48][49][50][51][52][53][54][55][56]. It has been found that the memory effect is difficult to detect directly with the current ground-based GW detectors, but the future groundbased detectors such as Cosmic Explorer [57] and Einstein Telescope [58] may be able to detect the memory effect [59].…”
Section: Introductionmentioning
confidence: 99%
“…The strategies for detecting the GW memory effect were first proposed by Braginsky and Thorne in the 1980s [13,40]. Since the first detection of GWs by LIGO in 2015 [41], many works about detecting memory effect with current and future GW detectors have appeared [30,[42][43][44][45][46][47][48][49][50][51][52][53][54][55][56]. It has been found that the memory effect is difficult to detect directly with the current ground-based GW detectors, but the future groundbased detectors such as Cosmic Explorer [57] and Einstein Telescope [58] may be able to detect the memory effect [59].…”
Section: Introductionmentioning
confidence: 99%
“…For the dependence of the memory on the spins, mass ratio and eccentricity, we refer the reader to Refs. [57,68,81,89,97,98].…”
Section: Ii2 Phenomenology Of the Signalmentioning
confidence: 99%
“…However, the prospects for memory detection in single events are considerably better for third-generation ground-based detectors (e.g. Einstein Telescope [64] and Cosmic Explorer [65]) and for the future space-based detectors LISA and Tian-Qin, due to their better sensitivity and low frequency coverage [54,62,[66][67][68][69]. 4 In this work we investigate the impact of the nonlinear memory on parameter estimation via a Fisher matrix analysis.…”
Section: Introductionmentioning
confidence: 99%